A kind of silk fibroin hydrogel and preparation method thereof

Silk fibroin microspheres were obtained by spray drying and ultrasonic cross-linking was performed in the solution of γ-polyglutamic acid and glutaraldehyde, which solved the problem of the short retention time of silk fibroin hydrogels and insufficient stability, and achieved higher mechanical strength and cross-linking methods suitable for industrial production.

CN119751929APending Publication Date: 2025-04-04WUXI YAXIN BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202411857450.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing silk fibroprotein hydrogels have too short retention time, insufficient stability and mechanical strength, which limit their application in the fields of biomedicine and biochemistry.

Method used

Silicone fibroin microspheres were obtained by spray drying, and ultrasonic cross-linked in a solution containing γ-polyglutamic acid (γ-PGA) and glutaraldehyde to form a silk fibroin hydrogel with good stability and mechanical strength.

Benefits of technology

It improves the retention time, stability and mechanical strength of silk fibroin, and the cross-linking method is simple, which is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751929A_ABST
    Figure CN119751929A_ABST
Patent Text Reader

Abstract

The present invention relates to a kind of silk fibroin hydrogel and preparation method thereof, silkworm raw silk is degummed, sol, dialyzed, filtered, freeze-dried to obtain silk fibroin freeze-dried powder, then redissolved into high concentration silk fibroin solution, filtered and spray-dried into silk fibroin microspheres; silk fibroin microspheres are slowly added to a phosphate buffered saline solution containing γ-polyglutamic acid and glutaraldehyde, stirred and ultrasonically carried out the first cross-linking, then a cross-linking agent solution is added, stirred evenly and ultrasonically, and the second cross-linking is carried out, and the silk fibroin hydrogel is obtained after being rinsed with pure water after being placed for a period of time. In the preparation method of the present invention, a phosphate buffered saline solution containing γ-polyglutamic acid and glutaraldehyde is used as a cross-linking agent and secondary cross-linking is carried out, and the prepared silk fibroin hydrogel silk fibroin has a long retention time, good stability and mechanical strength, and the cross-linking method is simple, and it is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and particularly relates to a silk fibroin hydrogel and a preparation method thereof. Background Art

[0002] Silk fibroin (SF) is a unique natural protein extracted from silk. It has excellent biocompatibility, adjustable biodegradation, low immunogenicity, excellent mechanical strength and easy access. Silk fibroin has become an excellent candidate material in tissue engineering. Its hydrogel has good water retention and can highly simulate the physical and chemical environment of the extracellular matrix. It is an ideal biological tissue engineering material.

[0003] As a typical hydrogel material, SF hydrogel has been widely used in related fields such as cell culture and tissue defect repair in vivo. The development of a simple method for SF hydrogel is particularly important for industrial production. Silk fibroin hydrogel is generally prepared by high temperature, low pH, chemical cross-linking and other methods. The cross-linking method is complex and diverse and is not suitable for large-scale industrial production. The prepared silk fibroin hydrogel has a short retention time, and its stability and mechanical strength need to be improved, which limits the application of silk fibroin hydrogel in biomedicine and biochemistry.

[0004] Chinese patent CN201410547861.1 discloses a composite silk fibroin hydrogel and its preparation method and application. In the preparation of the composite silk fibroin hydrogel, silkworm cocoons are uniformly shredded and added to a sodium carbonate solution, stirred and filtered, washed with deionized water, vacuum dried, dissolved with a calcium chloride aqueous solution, and the solution is placed in a dialysis bag, and then dialyzed in pure water to obtain a silk fibroin aqueous solution. Finally, the silk fibroin aqueous solution is used as a raw material and ultrasonically treated and stirred together with chitosan, polyvinyl alcohol, ethyl acrylate, and sodium alginate to obtain a composite silk fibroin hydrogel; other polymers are added to improve the tensile strength and swelling rate of the hydrogel, and its cross-linking is poor, thereby greatly reducing the mechanical properties, stability, and biodegradability. Summary of the invention

[0005] The purpose of the present invention is to provide a silk fibroin hydrogel and a preparation method thereof. The prepared silk fibroin hydrogel has a long silk fibroin retention time, good stability and mechanical strength, and a simple cross-linking method, and is suitable for large-scale industrial production.

[0006] The technical solution adopted by the present invention to solve the above problem is: a method for preparing a silk fibroin hydrogel, comprising the following steps: (1) Degumming The raw silk of silkworms is placed in a sodium carbonate solution for boiling and degumming, then washed with deionized water, and then dried to obtain refined silk; (2) Dissolution of refined silk The refined silk obtained in step (1) is placed in a lithium bromide solution or a calcium chloride solution for complete dissolution to obtain a mixed solution; (3) Dialysis and spray drying The mixed solution is filled into a dialysis bag, and then placed in deionized water or pure water for dialysis, and a regenerated silk fibroin solution is obtained after dialysis filtration, and the regenerated silk fibroin solution is freeze-dried and then redissolved into a high-concentration silk fibroin solution, and the high-concentration silk fibroin solution is filtered and spray-dried into silk fibroin microspheres and placed in a bottle for sealing and storage for later use, and the spray-dried silk fibroin powder is spherical particles with a random curl structure and water-soluble; (4) Cross-linking a. Prepare 0.1M phosphate buffered saline (PBS buffer), add γ-polyglutamic acid (γ-PGA), stir evenly, then add glutaraldehyde, and adjust the pH to 6-8 to obtain a crosslinker solution; b. Slowly add the silk fibroin microspheres prepared in step (3) to the crosslinking agent solution, stirring evenly and ultrasonicating at the same time, so that the silk fibroin microspheres are crosslinked with γ-polyglutamic acid (γ-PGA) and glutaraldehyde for the first time; c. Add the crosslinking agent solution, stir evenly and perform ultrasonic treatment to perform the second crosslinking. After standing for a period of time, rinse with pure water to obtain the silk fibroin hydrogel.

[0007] Preferably, the boiling degumming treatment in step (1) and the deionized water washing are repeated 2 to 4 times.

[0008] Preferably, in step (2), the dissolution temperature is 60-90°C and the dissolution time is 60-90 min.

[0009] Preferably, the lithium bromide solution in step (2) is a 9-10M lithium bromide aqueous solution, and the mass ratio of the lithium bromide solution to the refined silk is 9-11:1; the calcium chloride solution is a calcium chloride aqueous solution with a mass concentration of 35-45%, and the mass ratio of the calcium chloride solution to the refined silk is 47-55:1.

[0010] Preferably, the specific operation of step (3) is as follows: the mixed solution is filled into a dialysis bag with a molecular weight cutoff of 3000-10000 kDa, and then placed in 4°C deionized water or pure water for dialysis, the water is changed every 2 hours, and the process is continued for 3-4 days, and then filtered through a 200-400 mesh sieve to obtain a regenerated silk fibroin solution, the regenerated silk fibroin solution is freeze-dried and then redissolved into a high-concentration silk fibroin solution with a mass concentration of 10-30%, the high-concentration silk fibroin solution is filtered through a 200-400 mesh sieve in turn, spray-dried into silk fibroin microspheres, and placed in a bottle and sealed for storage.

[0011] Preferably, in the cross-linking agent solution in step (4), the mass concentration of glutaraldehyde is 0.2-0.5%, and the mass concentration of γ-polyglutamic acid (γ-PGA) is 5%.

[0012] Preferably, the molecular weight of the γ-polyglutamic acid (γ-PGA) in step (4) is 7000-10000.

[0013] Preferably, in step (4), the ratio of the glutaraldehyde solution to the silk fibroin microspheres in the first cross-linking is 0.7-1%, and the ratio of the silk fibroin microspheres in the second cross-linking, i.e. the final concentration, is 0.35-0.5%.

[0014] A silk fibroin hydrogel is prepared by the above-mentioned method for preparing the silk fibroin hydrogel.

[0015] Compared with the prior art, the advantages of the present invention are: (1) The present invention adds the spray-dried silk microspheres to a solution containing γ-polyglutamic acid (γ-PGA) and glutaraldehyde for ultrasonic cross-linking, and then rinses with pure water to obtain the silk fibroin hydrogel. The hydrogel can solve the shortcoming of the short retention time of silk fibroin and improve its stability and mechanical strength. The cross-linking method is simple and suitable for large-scale industrial production. It has high commercial application value in practical applications.

[0016] (2) The crosslinking agent used in the preparation process of the silk fibroin hydrogel of the present invention is a PBS buffer solution containing γ-polyglutamic acid (γ-PGA) and glutaraldehyde, wherein γ-polyglutamic acid (γ-PGA) can be chemically crosslinked with the active amino acids in the silk fibroin (SF) through a large number of carboxyl groups on its side chain (carboxyl groups form salt bonds or hydrogen bonds with active amino acids in the silk fibroin such as alkaline amino acids such as lysine), which not only enhances the mechanical properties and stability of the material, but also its biodegradability means that it can be gradually degraded in the body without toxic side effects on tissues, and glutaraldehyde reacts with amino groups or other active groups in the silk fibroin molecules through aldehyde groups to form covalent bonds, thereby connecting the silk fibroin molecules to a network structure, which not only enhances the mechanical properties of the silk fibroin, but also makes it have better water absorption and degradability. The simultaneous addition of γ-polyglutamic acid (γ-PGA) and glutaraldehyde can further greatly promote the crosslinking process, improve the crosslinking efficiency and quality, and thus obtain a composite hydrogel with better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The present invention is a flow chart for preparing the silk fibroin hydrogel.

[0018] Figure 2 This is a picture of the freeze-dried silk fibroin powder in Example 1 of the present invention.

[0019] Figure 3This is a picture of the silk fibroin microspheres in Example 1 of the present invention.

[0020] Figure 4 This is a picture of the silk fibroin hydrogel in Example 1 of the present invention.

[0021] Figure 5 It is a comparison chart of the water absorption and swelling rate of the silk fibroin hydrogels of Examples 1-2 of the present invention and Comparative Examples 1-5.

[0022] Figure 6 It is a comparison chart of the elastic modulus of the silk fibroin hydrogels of Examples 1-2 of the present invention and Comparative Examples 1-5. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below with reference to the accompanying drawings.

[0024] like Figure 1 As shown, this is the flow chart of the preparation of silk fibroin hydrogel in this embodiment. Example 1

[0025] A silk fibroin hydrogel and a preparation method thereof, comprising the following steps: Sodium carbonate degumming: Weigh 10g of raw silk from silkworms and place it in 500mL of a sodium carbonate solution with a mass concentration of 0.5g / L, boil and degumming for 30min, wash with deionized water, repeat the above degumming steps for 3 times, and finally dry it in an oven at 60℃ to obtain refined silk; Dissolution of refined silk: 10 g of refined silk was placed in 100 mL of 9.3 M lithium bromide aqueous solution, and slowly stirred for 60 min at a water bath temperature of 60°C until completely dissolved to obtain a mixed solution; Dialysis and spray drying: The mixed solution was filled into a dialysis bag (3000Da), placed in 4°C deionized water for dialysis, and the water was changed every 2 hours for 3 days. The regenerated silk fibroin solution was obtained after filtration through a 200-mesh sieve. The regenerated silk fibroin solution was freeze-dried (such as Figure 2 ) and then re-dissolved into a 10% silk fibroin solution, filtered through a 200-mesh screen, and then spray-dried into silk fibroin microspheres (as shown in Figure 3 As shown) and seal in a bottle for later use; Cross-linking a. Prepare 0.1M PBS solution, add γ-PGA and stir evenly, then add glutaraldehyde to prepare a crosslinker solution with a γ-PGA mass concentration of 5% and a glutaraldehyde mass concentration of 0.25%, and adjust the pH to 7; b. Slowly add 3.5 g of the silk fibroin microspheres prepared in step (3) into 50 ml of the crosslinking agent solution, stir evenly and perform ultrasonic treatment for 30 min to perform the first crosslinking of the silk fibroin microspheres with γ-polyglutamic acid (γ-PGA) and glutaraldehyde; c. Add 50 ml of crosslinker solution, stir evenly and ultrasonicate for 30 minutes to perform the second crosslinking. After standing overnight, rinse with pure water to obtain silk fibroin hydrogel (such as Figure 4 as shown). Example 2

[0026] Sodium carbonate degumming: Weigh 10g of raw silk from silkworms and place it in 500mL of a sodium carbonate solution with a mass concentration of 0.5g / L, boil and degumming for 30min, wash with deionized water, repeat the above degumming steps for 3 times, and finally dry it in an oven at 60℃ to obtain refined silk; Dissolution of refined silk: 10 g of refined silk was placed in 500 mL of 40% calcium chloride aqueous solution, and slowly stirred for 90 min in a water bath at 85°C until completely dissolved to obtain a mixed solution; Dialysis and spray drying: the mixed solution was filled into a dialysis bag (3000Da), placed in 4°C deionized water for dialysis, and the water was changed every 2 hours for 3 days. The solution was then filtered through a 200-mesh sieve to obtain a regenerated silk fibroin solution. The regenerated silk fibroin solution was freeze-dried and then re-dissolved into a 12% silk fibroin solution, which was then filtered through a 200-mesh sieve. The solution was then spray-dried into silk fibroin microspheres and sealed in a bottle for later use. Cross-linking a. Prepare 0.1M PBS solution, add γ-PGA and stir evenly, then add glutaraldehyde to prepare a cross-linking agent solution with a γ-PGA mass concentration of 5% and a glutaraldehyde mass concentration of 0.3%, and adjust the pH to 7; b. Slowly add 3.5 g of the silk fibroin microspheres prepared in step (3) into 50 ml of the crosslinking agent solution, stir evenly and perform ultrasonic treatment for 30 min to perform the first crosslinking of the silk fibroin microspheres with γ-polyglutamic acid (γ-PGA) and glutaraldehyde; c. Add 50 ml of crosslinker solution, stir evenly and ultrasonicate for 30 min to perform the second crosslinking. After standing overnight, rinse with pure water to obtain silk fibroin hydrogel.

[0027] Comparative Example 1 The only difference from Example 1 is that the regenerated silk fibroin solution in step (3) is slowly added to 50 ml of the cross-linker solution, that is, the steps of "freeze-drying the regenerated silk fibroin solution and then re-dissolving it into a 10% silk fibroin solution, filtering it with a 200-mesh sieve, and then spray-drying it into silk fibroin microspheres" are not performed in step (3).

[0028] Comparative Example 2 The only difference from Example 1 is that γ-polyglutamic acid (γ-PGA) is not added, that is, γ-polyglutamic acid (γ-PGA) is completely replaced by glutaraldehyde.

[0029] Comparative Example 3 The only difference from Example 1 is that glutaraldehyde is not added, that is, glutaraldehyde is completely replaced by γ-polyglutamic acid (γ-PGA).

[0030] Comparative Example 4 The only difference from Example 1 is that γ-polyglutamic acid (γ-PGA) is replaced by polyaspartic acid.

[0031] Comparative Example 5 The only difference from Example 1 is that glutaraldehyde is replaced by hexamethylenediamine.

[0032] The water absorption swelling rate and mechanical properties of the silk fibroin hydrogels of Examples 1-2 and Comparative Examples 1-5 were tested: The results of water absorption and swelling rate are as follows Figure 5 As shown, the water absorption and swelling rates of Examples 1 and 2 are the best, and the water absorption and swelling rates after cross-linking with glutaraldehyde and γ-polyglutamic acid (γ-PGA) are higher than those of other examples. As time goes by, the swelling rates tend to be stable, which is better than those in Comparative Examples 1-5.

[0033] The mechanical properties (elastic modulus) test is as follows: the sample is tested at room temperature using a microcomputer-controlled electronic universal testing machine with a load of 600 N and a compression speed of 10 mm / min. The sample diameter is 11 mm and the height is 20 mm. Three samples are measured in parallel to obtain the average elastic modulus and standard error.

[0034] The elastic modulus is Figure 6 As shown, the elastic moduli of Examples 1 and 2 are both higher than that of the comparative example.

[0035] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a silk fibroin hydrogel, characterized in that: The following steps are involved: (1) Degumming The raw silk of silkworms is placed in a sodium carbonate solution for boiling and degumming, then washed with deionized water, and then dried to obtain refined silk; (2) Dissolution of refined silk The refined silk obtained in step (1) is placed in a lithium bromide solution or a calcium chloride solution for complete dissolution to obtain a mixed solution; (3) Dialysis and spray drying The mixed solution is filled into a dialysis bag, and then placed in deionized water or pure water for dialysis, and a regenerated silk fibroin solution is obtained after dialysis filtration, and the regenerated silk fibroin solution is freeze-dried and then redissolved into a high-concentration silk fibroin solution, and the high-concentration silk fibroin solution is filtered and spray-dried into silk fibroin microspheres, and then placed in a bottle and sealed for storage; (4) Cross-linking a. Prepare 0.1M phosphate buffered saline solution, add γ-polyglutamic acid, stir evenly, then add glutaraldehyde, and adjust the pH to 6-8 to obtain a crosslinker solution; b. Slowly add the silk fibroin microspheres prepared in step (3) to the crosslinking agent solution, stirring evenly and ultrasonicating at the same time, so that the silk fibroin microspheres are crosslinked with γ-polyglutamic acid and glutaraldehyde for the first time; c. Add the crosslinking agent solution, stir evenly and perform ultrasonic treatment to perform the second crosslinking. After standing for a period of time, rinse with pure water to obtain the silk fibroin hydrogel.

2. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: The boiling degumming treatment in step (1) and the deionized water washing are repeated 2 to 4 times.

3. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In step (2), the dissolution temperature is 60-90°C and the dissolution time is 60-90 minutes.

4. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: The lithium bromide solution in step (2) is a 9-10M lithium bromide aqueous solution, and the mass ratio of the lithium bromide solution to the refined silk is 9-11:1; the calcium chloride solution is a calcium chloride aqueous solution with a mass concentration of 35-45%, and the mass ratio of the calcium chloride solution to the refined silk is 47-55:

1.

5. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: The specific operation of step (3) is as follows: the mixed solution is filled into a dialysis bag with a molecular weight cutoff of 3000-10000 kDa, and then placed in 4°C deionized water or pure water for dialysis, the water is changed every 2 hours, and the process is continued for 3-4 days, and then filtered through a 200-400 mesh sieve to obtain a regenerated silk fibroin solution, the regenerated silk fibroin solution is freeze-dried and then redissolved into a high-concentration silk fibroin solution with a mass concentration of 10-30%, the high-concentration silk fibroin solution is filtered through a 200-400 mesh sieve in turn, spray-dried into silk fibroin microspheres, and placed in a bottle and sealed for storage.

6. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: The mass concentration of glutaraldehyde in the cross-linking agent solution in step (4) is 0.2-0.5%, and the mass concentration of γ-polyglutamic acid is 5%.

7. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: The molecular weight of the γ-polyglutamic acid (γ-PGA) in step (4) is 7000-10000.

8. The method for preparing the silk fibroin hydrogel according to claim 1, characterized in that: In step (4), the concentration of the silk fibroin microspheres cross-linked for the first time is 0.7-1%, and the concentration of the silk fibroin microspheres cross-linked for the second time is 0.35-0.5%.

9. A silk fibroin hydrogel, characterized in that: The silk fibroin hydrogel is prepared by the preparation method of the silk fibroin hydrogel according to any one of claims 1-8.

Citation Information

Patent Citations

  • Composite silk fibroin hydrogel and preparation method and application thereof

    CN104327283A

Cited By

  • Preparation method of full-time controllable water-absorbing material and flow-state solidified soil building material prepared from full-time controllable water-absorbing material

    CN121085573A

  • Cross-linked gel microsphere reinforced silk fibroin composite gel as well as preparation method and application thereof

    CN121197538A

  • Acoustic power driven Janus hydrogel as well as preparation method and application thereof

    CN121731202A